Light-active azaphenalene alkoxyamines: fast and efficient mediators of a photo-induced persistent radical effect. Issue 83 (25th August 2016) - Bottle, Steven E.; Clement, Jean-Louis; Fleige, Mirco; Simpson, Emily M.; Guillaneuf, Yohann; Fairfull-Smith, Kathryn E.; Gigmes, Didier; Blinco, James P.
Abstract : Reported is the first example of an alkoxyamine that quantitatively yields a nitroxide upon light exposure. The alkoxyamine is used to generate a light driven persistent radical effect and applied to radical insertion, exchange and polymerization reactions. Abstract : Here we report the first example of an alkoxyamine derived from an azaphenalene nitroxide, which when exposed to UV-light, readily undergoes homolysis to efficiently and cleanly re-form a nitroxide. This process selectively cleaves the C–O bond of the alkoxyamine and occurs orders of magnitude more rapidly than any other alkoxyamine homolysis previously described in the literature. We demonstrate the use of light to generate a persistent radical effect (PRE) and apply this to undertake radical insertion, radical exchange and proof of concept polymerization reactions.